AB0905 Late-onset spondyloarthropathy mimicking polymalgia rheumatica: Evidence from MRI. (23rd January 2014) - Mackie, S.L.; Ash, Z.; Pease, C.T.; McGonagle, D.; Marzo-Ortega, H.
Abstract : Background: Polymyalgia rheumatica (PMR) is a clinical syndrome, typically affecting older people, presenting with inflammatory musculoskeletal symptoms. Late onset rheumatoid arthritis is a well-known PMR mimic, but spondyloarthropathy (SpA) can also present with PMR symptoms [1]. Magnetic resonance imaging (MRI) may show extracapsular inflammation of peripheral joints in both diseases [2]. Objectives: To describe the clinical and MRI findings in four patients who presented with polymyalgic features but who evolved to a SpA-like picture. Methods: Four cases are presented and common features identified. Results: Three men and one woman, aged 64, 58, 63 and 55, each presented with polymyalgic symptoms of several months' duration affecting shoulder and hip girdles, associated with prolonged early morning stiffness. Onset was gradual in 3 cases. All subjects had back pain symptoms at presentation (lumbar in cases 1, 2; thoracic in case 4; right iliac crest in case 3). Comorbidities included migraine, glaucoma and carcinoma of the prostate (case 1); hypertension and ischaemic heart disease (case 2), chronic obstructive pulmonary disease (cases 2 and 3); and bronchiectasis (case 4). Symptoms were preceded by a chest infection in case 4 and weight loss in Cases 1 and 2. Inflammatory markers were elevated in all (plasma viscosity was 1.92 mPas in case 1; CRP was 33, 29 and 22 mg/L in cases 2, 3 and 4). Case 1 later developed biopsy-proven giant cell arteritis with visual aura. Initial clinical and laboratory response to steroid treatment was satisfactory in all. However, treatment withdrawal led to recurrence of inflammatory back pain which remained a prominent symptom in all cases, with mixed response to COX-II selective inhibitors. MRI showed: florid osteitis of sacro-iliac joints and entheseal lesions at the manubriosternal and sternoclavicular joints (Case 1), irregularity of sacro-iliac joints and vertebral corner lesions (Case 2), sacro-iliac joint erosions and vertebral corner lesions (Case 3) and entheseal lesions at the ischial tuberosity and gluteus medius insertions (Case 4). All MRI appearances were typical of SpA. Currently, only case 3, which is also the only HLA-B27 positive case, fulfils the modified New York Criteria for ankylosing spondylitis. Steroid-sparing agents have recently been initiated in two cases (methotrexate for Case 1, sulphasalazine for Case 4). Conclusions: These cases illustrate a polymyalgic presentation of late-onset SpA subsequently confirmed on MRI, with osteitis and enthesitis lesions reminiscent of SpA. PMR remains a diagnosis of exclusion with a lack of pathognomonic or specific features. Physicians should remain vigilant if faced with recalcitrant symptoms or difficulty in steroid reduction. These preliminary findings raise the possibility that MRI may have a role in more accurate differentiation of PMR from late-onset SpA and has potential implications for diagnosis and disease stratification. References: Olivieri, I., et al., Late onset undifferentiated spondyloarthritis presenting with polymyalgia rheumatica features: description of seven cases. Rheumatol Int. 2007;27:927-33. Marzo-Ortega, H., et al., Evidence for a different anatomic basis for joint disease localization in polymyalgia rheumatica in comparison with rheumatoid arthritis. Arthritis Rheum. 2007;56:3496-501. Disclosure of Interest: None Declared